Growth, Cost and Carcass Evaluation of Snail (Archachatina marginata) Fed Diet Containing Yam Peel-Soy-Bean Residue Mixture Meal - Popoola, Y. A.; Owosibo, A. O.; Ogunleke, F. O.; Idowu, A. B.; Omole, A. J. (European Journal of Applied Sciences, 2024)
The study was conducted to determine effect of inclusion of dry Yam peel-soybean residues meal (YPSM) as substitute to Maize in the diet of snail (Archachatina marginata). A total of 120 growing snails (average weight of 76.5 ± 2.4g, 4 months old) were used for the study. Four dietary treatments comprising Yam peel-soybean residue meal (YPSM) replaced maize at 0% (YPSM1), 50% (YPSM 2), 75% (YPSM3) and 100% (YPSM4) were compounded and allotted to snails in a completely randomized design. Data were collected on growth performance, reproductive indices, cost implications and carcass yield were statistically analyzed using analysis of variance. There was no significant difference in the mean total feed intake in YPSM1, YPSM2 and YPSM3 (P>0.05). The mean total weight gain was significantly different across the treatments (P<0.05) although no significant difference in the mean total weight gain in YPSM1, YPSM2 and YPSM3. The mean shell length was not significantly influenced by dietary treatments and the values ranged between 12.68 in YPSM1 and 12.48 in YPSM4. Shell width and thickness were not significantly different from one another as the level of YPSM in the diet increased (P>0.05). The lowest cost/weight gain was recorded in the diet containing 75% YPSM as replacement for maize while the highest cost/weight gain was recorded in the diet containing 100%YPSM. Based on the results obtained from this study, it could be recommended that Yam peel-soybean residues meal (YPSM) could be included up to 75% as replacement for maize fraction of the diet of snail (Archachatina maginata) without adverse effect but at reduced cost.